Empowering Reflection and Reflective Writing in Medical Education - Dharmasaroja, Permphan (Ramathibodi Medical Journal, 2024)
Reflection and reflective writing serve as integral components in medical education. They enable students to delve deeper into their experiences, fostering a profound understanding of clinical scenarios and patient interactions, nurturing self-awareness, critical thinking, and empathy. The term “reflection” carries multiple interpretations, all encapsulating the concept of understanding oneself and the surrounding environment to inform future behavior. In the realm of medical education, both students and medical teachers encounter challenges in navigating reflective practices, necessitating guidance and support throughout the process. Effective reflection between students and medical teachers in clinical settings requires adept navigation through potential difficulties in open discussions and managing the emotional impact. To address these challenges, medical teachers must possess heightened self-awareness and adaptability to cater to the diverse needs of individual students. Various models have offered frameworks to organize the reflective process, categorizing them into ‘iterative’ and ‘vertical’ approaches. Successful application involves a selective combination of elements from different models to customize reflective practices. Comprehending reflection and reflective writing is paramount for medical teachers as it empowers them to mentor students effectively, nurturing a culture of reflective practitioners. This fosters continual learning, ethical practice, and professional development among future healthcare professionals.